Comparative Analysis of Phase Change Materials as Solar Thermal Energy Storage for Yogurt Incubation - Sinha, Chitranayak; Prateek; Ray, Arijit; Minz, P. S.; Priyanka; Kumari, Khushbu (International Journal of Bio-resource and Stress Management, 2025)
A study was conducted during October, 2022 to June, 2023 at National Dairy Research Institute, Karnal, Haryana, India to evaluate the thermal performance and melting behaviour and the effect of different container materials on energy storage efficiency of phase change materials (PCMs). Paraffin wax, Beeswax and Palm oil was selected for this study and for the container material stainless steel (SS) and polyethylene terephthalate (PET) was selected. The results indicated that PET containers, although slower to heat (100 min), provide a prolonged cooling period (240 min), making them ideal for applications that require delayed heat release. Among the PCMs, Paraffin wax, with a melting temperature of 59.3°C and a melting time of 36 min, was found to be the most suitable for solar thermal applications. Beeswax, while viable, had a higher melting temperature (68.1°C) and a longer melting time (48 min). Palm oil, with a melting temperature of 43°C, was deemed unsuitable. Image analysis confirmed these findings, showing that palm oil had the highest reduction rate in area and perimeter, while all three PCMs displayed favourable roundness values. Based on the results, Paraffin wax in PET containers was identified as the optimal combination for efficient solar energy storage.